Conciliation in settling administrative recourses according to the regulations of the Latin Church - MIZIŃSKI, ARTUR (Prawo Kanoniczne, 2012)
Protection of the rights of physical and legal entities belongs to the principal functions of the authorities and the legal system of each social organism. A new look at the Church, especially after the Vatican Council II, encouraged far reaching protection of subjective rights in the Church. The available measures that are now provided for by the code legislator and whose direct aim is to prevent the occurrence of an administrative recourse in the formal sense include seeking from the author of the act the revocation or amendment, addressing mediators, referring the matter to be examined by an office or council established by the conference of bishops or a particular bishop (can. 1733-1734). The material scope of the acts against which conciliatory measures can be instituted in the Church was determined in can. 1732. These are all singular administrative acts, especially decrees and concrete orders issued in the external forum outside a trial except those which have been issued by the Roman Pontiff or an ecumenical council. A request to the author of an administrative act for revocation or amendment, aimed at avoiding obedience to it in life, is not an ordinary request for favour since it places an obligation upon the author to take an attitude again to the whole matter being the object of the act (can. 1734 § 1). Mediation means the parties in danger of a conflict turning to serious-minded persons enjoying authority with a request to settle the recourse, at the same time making an obligation to subordinate to the solution suggested by them (can. 1733 § 1). Moreover, the legislator of the code provides the Conferences of bishops with the right to establish in a stable manner an office or council whose task would be to seek and suggest equitable solutions and to lay down the norms regulating the work of these bodies. Should the Conference not use this right, such a council can be established by the bishop for his Church (can. 1733 § 2-3).